2014
DOI: 10.1002/adfm.201470042
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Materials: Domain Wall Displacement is the Origin of Superior Permittivity and Piezoelectricity in BaTiO3 at Intermediate Grain Sizes (Adv. Funct. Mater. 7/2014)

Abstract: Domain walls in ferroelectrics are moved by the application of electric fields by J. L. Jones and co-workers. The extent of this domain wall motion can be measured using high-energy X-ray diffraction. During the application of electric fields, DebyeScherrer cones diffract from the sample in transmission geometry. On page 885, the corresponding diffraction rings are measured on an area detector, and the contribution of domain walls to properties and functional behavior can thereby be analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Very recently, N. Liu et al showed the existence of low-permittivity paraelectric grain boundary can be a key factor leading to the unusual overall hysteresis behavior of barium titanate (BaTiO 3 ) ceramics. D. Ghosh et al validated the contribution of domain wall motion to macroscopic property coefficients in BaTiO 3 ceramics with intermediate grain sizes using high-energy XRD technique [5]. However, experiments directly measuring the effect of domain wall motion on macroscopic properties in ferroelectric ceramics with different grain sizes have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, N. Liu et al showed the existence of low-permittivity paraelectric grain boundary can be a key factor leading to the unusual overall hysteresis behavior of barium titanate (BaTiO 3 ) ceramics. D. Ghosh et al validated the contribution of domain wall motion to macroscopic property coefficients in BaTiO 3 ceramics with intermediate grain sizes using high-energy XRD technique [5]. However, experiments directly measuring the effect of domain wall motion on macroscopic properties in ferroelectric ceramics with different grain sizes have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%